1983
DOI: 10.2307/2259607
|View full text |Cite
|
Sign up to set email alerts
|

Hypochoeris Radicata L. (Achyrophorus Radicatus (L.) Scop.)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Section: Hypochoeris. Herbaceous perennial growing from hard, thickened, overwintering base (caudex); fibrous-rooted, but often with several enlarged roots, and appearing tap-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…restricted to warmer conditions at low elevation and others (e.g., Hypochaeris radicata, Plantago lanceolata, and Rumex acetosella) capable of establishing viable populations at the highest elevations. Independent data show that this latter group is largely composed of species with broad climatic amplitudes (28,(30)(31)(32). As a result, the nonnative floras of higher elevations are composed of nested sets of species with increasingly wide elevational amplitudes, a process we call directional ecological filtering.…”
Section: Discussionmentioning
confidence: 99%
“…restricted to warmer conditions at low elevation and others (e.g., Hypochaeris radicata, Plantago lanceolata, and Rumex acetosella) capable of establishing viable populations at the highest elevations. Independent data show that this latter group is largely composed of species with broad climatic amplitudes (28,(30)(31)(32). As a result, the nonnative floras of higher elevations are composed of nested sets of species with increasingly wide elevational amplitudes, a process we call directional ecological filtering.…”
Section: Discussionmentioning
confidence: 99%
“…As Turkington & Aarssen (1983) commented with respect to the occurrence of H. radicata in Great Britain, it is very difficult to establish what are native populations for such a successful invasive species. We hypothesize that, on the basis of our results, the heterocarpic ancestral populations of H. radicata expanded out of northern Africa via a series of stepping stones across the Strait of Gibraltar area into the southern Iberian Peninsula in the Quaternary.…”
Section: Natural Distributional Area Of H Radicatamentioning
confidence: 99%
“…Hypochaeris radicata is a very successful colonizing species that now has a presence on virtually all continents. Beyond its probable native area in the Mediterranean region, where it occurs in relatively sparse populations associated with humid evergreen woodland, H. radicata is a successful invasive weed in Northern and Central Europe, where it is apparently very flexible with regard to soil requirements and growth conditions (Turkington & Aarssen 1983), and recent studies in southeastern Australia showed that H. radicata is one the most common dicotyledonous plants of temperate perennial pastures (Dellow et al 2002). Likewise, Doi et al (2006) found H. radicata in all parts of temperate Japan, commonly in grasslands, with a distribution that is still expanding, and this species is also very common in South America (Cabrera 1971(Cabrera , 1978(Cabrera , 1987 with populations comprising large numbers of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the exposure time on an hourly time scale because the opening and presentation of a flower of H. radicata lasts for 3–7 h, and the pollen transport by pollinators is likely to be completed within a day.…”
Section: Resultsmentioning
confidence: 99%
“…We also have plotted typical results of f a transitions from consecutive force measurements of fresh and aged pollen grains under fluctuating relative humidity (RH) (Figure 2c,d). We focused on the exposure time on an hourly time scale because the opening and presentation of a flower of H. radicata lasts for 3−7 h, 23 and the pollen transport by pollinators is likely to be completed within a day.…”
Section: ■ Resultsmentioning
confidence: 99%